Podzemna zgradba različnih tipov vrtač v Sloveniji - Stefanovski, Sašo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2025)
Dolines are characteristic karst landforms, yet their subsurface structure remains insuffi-ciently understood. This study applies electrical resistivity tomography (ERT) to examine the link between surface morphology and subsurface structure of four doline types in Slovenia. We conducted 24 ERT surveys on twelve dolines in four areas: Kras (bowl-shaped), Kočevski Rog (well-shaped), Logatec–Begunje plain (funnel-shaped), and Loški Potok (elongated dolines). Two perpendicular profiles were measured per doline. Results reveal heterogeneity: morphologically similar dolines within one area displayed different subsurface structures, while morphologically different dolines across areas showed simi-larities. Three dolines contained vertical and subhorizontal low- to intermediate-resis-tivity zones beneath their floors, which likely indicate cave passages filled with sediment, suggesting varied morphogenesis of the analysed dolines. Doline surface form does not directly reflect their subsurface structure; local geological and geomorphological factors and morphodynamic processes have the strongest influence on doline development.
Keywords: geofizika; geomorfologija krasa; geophysics; karst; karst geomorphology; kras; morfogeneza; morphogenesis; sediment